The interplay of polarizable water and protein in the activation of the M2 channel - Gődény, Márta; Kovács, Nóra; Aman, Aamir; Rungrotmongkol, Thanyada; Schröder, Christian (Frontiers in Pharmacology, 2025)
The M2 proton channel within the Influenza A virus constitutes an essential element for viral replication, with its functionality depending on the protonation states of four histidine residues located within the channel. This study meticulously investigates the impact of polarizability on the channel’s gating dynamics across various protonation states, employing both polarizable and non-polarizable models for water, protein, and membrane. Through a comprehensive analysis, we elucidate the nuanced role of polarizability in the channel’s operational mechanisms, differentiating between the solvent and protein polarizable effects. This investigation not only enriches our understanding of the M2 channel’s biophysical behavior but also highlights the significance of polarizability.